Monkeypox viral detection in semen specimens of confirmed cases: A systematic review and meta‐analysis. Issue 1 (3rd November 2022) - Reda, Abdullah; Abdelaal, Abdelaziz; Brakat, Aml M.; Lashin, Basant Ismail; Abouelkheir, Moustafa; Abdelazeem, Basel; Rodriguez‐Morales, Alfonso J.; Sah, Ranjit
Abstract: The current literature shows increasing concerns about potential seminal transmission of monkeypox virus (MPXV). Accordingly, we aimed to understand better the potential presence of MPXV in the seminal fluids and others specimens obtained from MPX cases. On June 26, 2022, a systematic search of the literature was conducted to find articles that examine the presence of MPXV in the seminal fluid of confirmed cases. The search was updated once on August 12 and another on October 12, 2022, to include newly published articles. The prevalence of MPXV DNA presence in the seminal fluid and other specimens was pooled in a meta‐analysis (from studies with sample size > 5 to reduce overestimation) and results were presented as effect sizes (ES) and their corresponding 95% confidence intervals (CI). Nine articles were included. Only five studies were eligible for a meta‐analysis, and the pooled prevalence of MPXV DNA in semen specimens was 72.4% (95% CI: 55.7%−84.5%) among 115 patients. The positive rate of MPXV viral polymerase chain reaction (PCR) was higher among skin samples (89%; 95% CI: 78.2%−94.8%; N  = 62; studies = 2), followed by anogenital/rectal samples (74.3%; 95% CI: 60.4%−84.5%; N  = 54; studies = 2). On the other hand, the positivity rate was lower in nasopharyngeal (62.4%; 95% CI: 20.4%−91.5%; N  = 587; studies = 3), urine (21.1%; 95% CI: 4.3%−61.1%; N  = 617; studies = 4), and blood/plasma (14.3%; 95% CI: 11.3%−18.1%; N  = 609; studies = 3) samples. Besides, MPXV can be detected in semen early from Day 1 and up to 19 days after symptoms onset. Finally, two articles investigated the infectivity of MPXV particles detected in seminal specimens by testing their replication competence. Culturing MPXV was successful in two out of four patients included in these studies. MPXV is highly prevalent in seminal specimens of MPX cases, further corroborating the role of sexual transmission of the disease. However, further evidence is still needed to shed more light on the replication competence of these particles.